2019
DOI: 10.2105/ajph.2019.305222
|View full text |Cite
|
Sign up to set email alerts
|

Causal Language in Health Warning Labels and US Adults’ Perception: A Randomized Experiment

Abstract: Objectives. To examine US adults’ reactions to health warnings with strong versus weak causal language. Methods. In 2018, we randomly assigned 1360 US adults to answer an online survey about health warnings for cigarettes, sugar-sweetened beverages, or alcohol. Participants rated 4 warning statements using different causal language variants (“causes,” “contributes to,” “can contribute to,” and “may contribute to”) displayed in random arrangement. Results. Most participants (76.3%) selected the warning that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…In total, we identified 27 papers that fit our inclusion criteria (see Appendix A for PRISMA diagram) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. One paper reported on two studies using different methodologies to study the same variables [ 50 ], and four papers reported on different aspects of one intervention [ 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, we identified 27 papers that fit our inclusion criteria (see Appendix A for PRISMA diagram) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. One paper reported on two studies using different methodologies to study the same variables [ 50 ], and four papers reported on different aspects of one intervention [ 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of study aims and studied independent variables, five papers (19%) compared only new or enhanced labels with no or regular labels [ 51 , 52 , 53 , 54 , 63 ]. Focusing on label content, eight papers (30%) compared text-only labels with text and image labels [ 55 , 56 , 61 , 62 , 64 , 65 , 66 , 67 ], twelve studies (44%) compared text message characteristics (e.g., content, specificity, framing, source, use of causal language) [ 57 , 58 , 59 , 60 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and three (11%) compared image characteristics [ 57 , 66 , 75 ]. Four (15%) papers compared label formats, such as size, position, colour or branding [ 50 , 64 , 70 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After viewing the warnings and responding to survey items, participants completed two additional experiments (30,31) and answered demographic items. Participants received $2.20 for completing the survey.…”
Section: Methodsmentioning
confidence: 99%
“…25 We have previously reported additional details on the recruitment and other methods for our study. 26,27…”
Section: Methodsmentioning
confidence: 99%